Empirical evidence and state of practice of software agile teams. Issue 9 (13th August 2014) - Papatheocharous, Efi; Andreou, Andreas S.; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT The paper provides an in depth analysis of empirical evidence on the state of practice within the agile domain obtained through a survey conducted in 2012. The context of focus is agile software processes and teams and the particular topics of interest revolve around three axes: (i) communication; (ii) project management; and (iii) quality assurance and validation. The aim of the survey is to deliver the current levels of agile adoption and practices as these are recorded in the responses of professionals in IT services and the software industry. The goal of the survey is to provide evidence‐based assessment of the level of agile adoption by software development organizations, in relation to the general profile of the respondents (country of origin, business sectors, roles, etc.) and compared with different types of practices followed, such as agile techniques adopted, team organization and communication techniques, and project management. Particular patterns and trends are identified in the survey connecting the use of the agile paradigm with the aforementioned practices and investigating its relation with the roles of the respondents and the business strategies of their organizations. Copyright © 2014 John Wiley & Sons, Ltd.